Effect of therapeutic massage on pain in patients with dementia. (January 2017) - Kapoor, Yamini; Orr, Robin
Introduction: The aim was to investigate whether therapeutic massage was effective in relieving pain in elderly residents with dementia. Methods: A randomized controlled study was conducted in an aged care facility. Ten participants with dementia or advanced dementia were allocated to an intervention group or a control group. The intervention group received 10 min of massage (effleurage, kneading, and trigger point therapy) four times per week for 4 weeks. The Pain Assessment in Advanced Dementia scale was used as the outcome measure. Results: No significant changes in mean outcome measure scores were found post intervention (Intervention mean = 5.0 ± 3.49; Control mean = 5.2 ± 3.49: t (8) = 0.09, p  = 0.93). However, the Intervention Group had a greater magnitude of change (1.200 ± 1.78) when compared to the control group (0.800 ± 2.16). Conclusion: Therapeutic massage may provide a useful adjunct to the current pain management plan of patients with dementia.